A Cubic Hermite variable fractional delay filter - Soontornwong, Parinya; Chivapreecha, Sorawat; Pradabpet, Chusit (My University, 2011)
This paper presents a design and realization of cubic Hermite variable fractional delay (VFD) filter. Cubic Hermite interpolation will be formulated to cubic Hermite VFD filter which the amplitude response and delay response of proposed cubic Hermite VFD filter depend on the used approximation of first derivative. The structure realization of cubic Hermite VFD filter is shown based on Farrow structure as well. Finally, the amplitude response and delay response of the proposed cubic Hermite VFD filter will be compared with the cubic B-spline and Lagrange-type VFD filter. © 2011 IEEE.
Keywords: cubic Hermite interpolation; digital filter; interpolation filter; variable fractional delay filter